Fleet of Drones in a Customized and Flexible Production System - Olivares-Chiappa, V (Institute of Electrical and Electronics Engineers Inc., 2024)
This work complements other previous studies and developments carried out by the authors on specific applications of (Unmanned Aerial Vehicle, UAV) at an industrial level for the operation of a fleet of drones within a production plant characterized by the customization of products in a flexible production system of large productive volumes. In particular, the problem of determining the drone fleet for this type of flexible and personalized production plant that allows demand to be met is addressed. A Case Study developed in a Plastic Manufacturing Company is presented, through a drone fleet management model based on energy efficiency, and its implementation according to annual, monthly, daily and shift planning. Different scenarios are considered in estimating the size of the drone fleet, including the variation in demand for final products, variability of critical process parameters, load coefficient for different demands and availability of the drone and the fleet. © 2024 IEEE.